THE COMPARISON USING DRAW LABEL CAPTION (DLC) AND DRILL TECHNIQUE TOWARD STUDENTS’ ENGLISH WRITING ABILITY - Fitri Palupi Kusumawati; Eva Faliyanti (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
Writing can be said that it is very important for the students, because the students can express their ideas and cxperience in writing form. The teachers should always look for which one suitable technique to be applied to the students, in order to make the students interested in learning writing, they are Draw Label Caption (DLC) and Drill Technique. In this research, the researcher compared DLC and Drill techniques that can be used to improve students’ writing ability. In this experimental research, there were 3 variables. That are 1). Draw Label Caption (DLC) technique as the first independent variable. 2). Drill technique as the second independent variable. 3) Writing skill as the dependent variable. The method that used in this research was test. Students were asked to write the text in English based on predetermined theme. In this study, researcher used pretest and Posttest. Based on the data analysis the researcher got the result of based on the calculation, it was found that: 1) F-ratio = 7.5 and F-table at significance level 1% was 7.08 and at significance 5% was 4.00. At this point the researcher found that F-ratio was bigger than F-table. The researcher concluded that there was difference of students’ English writing ability through DLC and Drill technique. 2) Fratio = 37.7 at the same signifficance level. In other words, there was difference of students’ English writing ability through DLC and Drill technique